EFFECTS OF NUTRITIONAL INTERVENTION IN PATIENTS HAVING ABDOMINAL SURGERY WITH PREPARATION (Vietnam Journal of Community Medicine, 2026)
Surgical patients require adequate nutrition to reduce complications and promote wound healing; however, optimizing nutrition is a difficult issue both theoretically and practically.Objective: To evaluate the effectiveness of nutritional intervention using a commercially available formula for patients undergoing planned abdominal surgery.Methods: A randomized controlled trial was conducted in Thai Binh province from January 2023 to October 2024, involving 54 individuals in the intervention group supplemented with Leanmax formula (57g/serving mixed in 180ml water, twice daily for 2 months) and 54 individuals in the control group with a normal diet.Results: The intervention group showed several positive differences compared to the control group; statistically significant differences (p0.05) were: less frequent respiratory infections (3.7%), less frequent urinary tract infections (5.6%), less frequent constipation (1.9%), less frequent nausea (9.3%), and less frequent itching (14.8%).Conclusion: Supplementing Leanmax formula for patients undergoing planned abdominal surgery reduces hospital stay, decreases infection rates, and improves nutrition, digestion, and overall health.
Keywords: SGA, abdominal surgery, postoperative, nutrition, micronutrient